1976
DOI: 10.1136/pgmj.52.604.95
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis and hyperparathyroidism

Abstract: Three patients with acute pancreatitis were found also to have hyperparathyroidism, two of them also formed pancreatic cysts. There appears to be more than an incidental relationship between the two diseases. The importance of serum calcium estimations in patients with pancreatitis is stressed. Theories as to why these diseases co-exist are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1977
1977
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…It has recently been suggested that the incidence of pancreatitis related to primary hyperparathyroidism might be underestimated in the United Kingdom (Rosin, 1976). In this respect it is worth re-emphasizing that an elevated serum calcium may be reduced to normal values during acute pancreatitis and only when the pancreatitis has settled down does the elevated calcium level, become apparent.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that the incidence of pancreatitis related to primary hyperparathyroidism might be underestimated in the United Kingdom (Rosin, 1976). In this respect it is worth re-emphasizing that an elevated serum calcium may be reduced to normal values during acute pancreatitis and only when the pancreatitis has settled down does the elevated calcium level, become apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Rosin (1976) reports three such cases, two of whom also formed pancreatic cysts, and gives a detailed review of this subject.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…Οι εκδηλώσεις της νόσου προέρχονται από τα αυξημένα ποσά ασβεστίου, με ανορεξία, ναυτία, δυσκοιλιότητα, μυϊκή αδυναμία και εύκολη κόπωση, πολυδιψία, πολυουρία και ψυχικές διαταραχές. Από τους νεφρούς συχνή είναι η νεφρολιθίαση (σε ποσοστό έως 70% των περιπτώσεων), που μπορεί να είναι μονήρης, πολλαπλή, ετερόπλευρη ή αμφοτερόπλευρη, ενώ πολλές φορές είναι υποτροπιάζουσα(109) και η νεφρασβέστωση (5% των περιπτώσεων με νεφρικές εκδηλώσεις), από τους οφθαλμούς συχνά υπάρχουν αλλοιώσεις του κερατοειδούς και εναπόθεση ασβεστίου στους επιπεφυκότες.Από τα οστά η αυξημένη παραθορμόνη προκαλεί απορρόφηση του οστίτου ιστού, με αντικατάσταση του από ινώδη ιστό (ινώδη κυστική οστεΐτις) και σχηματισμό κύστεων, που συχνά προκαλούν αυτόματα κατάγματα.Σπανιότερα η υπερασβεστιαιμία εκδηλώνεται με υπέρταση (20-50%), καρδιακές αρρυθμίες, νεφρική ανεπάρκεια, πεπτικά έλκη (10-15%), ή οξεία παγκρεατίτιδα (5-7% των περιπτώσεων με πρωτοπαθή υπερπαραθυρεοειδισμό)(107) .Η διάγνωση του πρωτοπαθούς υπερπαραθυρεοειδισμού τίθεται σχετικά εύκολα από την κλινική εικόνα και από τις μετρήσεις του ασβεστίου στο αίμα (υπερασβεστιαιμία) και του φωσφόρου (υποφωσφαταιμία). διαταραχών, ενυδάτωση και διούρηση), έχει θέση και εφαρμόζεται μόνο προσωρινά σε υπερασβεστιαιμική κρίση με υψηλές τιμές ασβεστίου, μέχρι να επιβεβαιωθεί η διάγνωση.…”
unclassified